Turning back to turkey - or turning the back to Germany? Remigration intentions and behavior of Turkish immigrants in Germany between 1984 and 2011 - Claudia Diehl; Elisabeth Liebau (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
By applying event-history analysis to all available waves of the German Socio-Economic Panel, we analyze how remigration intentions and actual remigration of Turkish migrants to Germany have evolved over time. The study draws from a broad set of theoretical approaches to remigration and it takes a different focus than previous studies by concentrating on long-term change in these rates. Our findings reveal an increase in remigration intentions and rates for first generation migrants after the turn of the millennium. Those who plan to return have a stronger emotional attachment to Turkey than those who plan to stay. Nevertheless, the two groups differ neither with respect to their educational levels nor in terms of their identification with Germany and perceptions of discrimination. Similarly, the small though slightly increasing group of immigrants that actually returns does not have a clear profile in terms of educational level, national identification, and perceptions of being disadvantaged in Germany. We thus argue that for first-generation migrants from Turkey after 2001, rising remigration intentions and actual remigration are unrelated to their integration into German society. Rather, the increase seems to be triggered by macro-structural changes in the country of origin.
Keywords: 650